SALES MANAGEMENT SYSTEM FOR ADDITIONAL SERVICES ON THE RETAIL LENDING MARKET - Sergey A. Krasko (Статистика и экономика, 2016)
The article presents the main issues of design sales management system for additional services on the retail lending market. Attention is concentrated on developing effective system architecture and conceptual provisions of the development.